Is 1,25-dihydroxyvitamin D3 receptor expression a potential Achilles’ heel of CD44+ oral squamous cell carcinoma cells? - Grimm, Martin; Alexander, Dorothea; Munz, Adelheid; Hoffmann, Jürgen; Reinert, Siegmar (Targeted oncology, 2013)
The aim of this study was to analyse the expression of 1,25-dihydroxyvitamin D3 receptor (VDR) in oral cancers are squamous cell carcinomas (OSCC) to evaluate whether oral tissue may be a new potential target for biologically active 1,25-(OH)2D3 or its analogues. Expression of VDR was analysed in OSCC specimen (n = 191) and cancer cell lines (BICR3, BICR56) by immunohistochemistry, real-time polymerase chain reaction (RT-PCR) analysis, and Western blotting. Scanned images were digitally analysed using ImageJ and the immunomembrane plug-in. VDR expression on protein level was correlated with proliferation marker Ki-67, clinical characteristics and impact on survival. VDR was co-labelled with CD44 and Ki-67 in double labeling experiments. Expression subgroups were identified by receiver operating characteristics (ROC) analysis. Low VDR expression was significantly associated with recurrence of the tumour. Multivariate analysis demonstrated low VDR expression as an independent prognostic factor (p = 0.0005). Immunohistochemical double staining revealed VDR expression by CD44+ cancer cells. An inverse correlation of VDR+ expressing cancer cells with Ki-67 has been found, which was indicated by immunofluorescence double labeling. VDR specificity was confirmed by Western blot and RT-PCR analysis. For the first time, our study provides evidence that decreased VDR expression in OSCC might be associated with tumour relapse. Tumour cells of a putative CD44+ cancer stem cell compartment express VDR indicating a potential Achilles’ heel for the treatment of OSCC although, our results do not allow any conclusion on the function of VDR. Adjuvant chemoprevention by using 1,25-(OH)2D3 or its analogues can be a successful tool targeting adjuvant residual tumour cells and will likely help therapeutic optimization for cancer patients in the clinic. However, this hypothesis requires further in vitro and in vivo studies.
Im Titel ist die Zahl 3 tiefgestellt
Gesehen am 25.02.2020